KEPATUHAN PENGGUNAAN RUANG KHUSUS MEROKOK: STUDI KOMPARATIF KOMPLEKS BALAI KOTA YOGYAKARTA DAN BANDARA ADISUTJIPTO YOGYAKARTA - Erdhianto Arya Pratama (Yogyakarta State University, 2018)
Yogyakarta is one of Indonesian’s regions that has implemented the smoking ban policy. One of the points of this policy is to regulate the provision and using the smoking room in public spaces. The aim of this study is to describe for what extent that smokers complied using smoking room and the factors that affect the compliances. This study used a qualitative descriptive method. Based on the research results, it can be concluded that smokers have a very diverse compliance. Smokers in City Hall of Yogyakarta have a very low compliance in the use of smoking room. On the other hand, Yogyakarta Adisucipto Airport smokers have a quite high compliance in the use of smoking room. There are five factors used to explain this study. Awareness, attitudes, and perceptions of the law or punishment proved significantly affect to a person's compliance. These three factors have a parallel relationship to the compliance. Education and age are not proved to give effects on compliance. Both of them do not have a significant effect and does not guarantee that there will always affect a person’s compliance.